2015
DOI: 10.1111/dme.12649
|View full text |Cite
|
Sign up to set email alerts
|

Associations of depression with impaired glucose regulation, newly diagnosed diabetes and previously diagnosed diabetes in Chinese adults

Abstract: Previously diagnosed diabetes, but not newly diagnosed diabetes or impaired glucose regulation, was associated with a higher prevalence of depression. Patients receiving insulin were more likely to have depression than those not receiving treatment or being treated with oral anti-diabetic medicine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
3
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 31 publications
(57 reference statements)
2
29
3
1
Order By: Relevance
“…In a large cross-sectional Chinese study, only people with previously known diabetes showed elevated depressive symptoms and more people treated with insulin showed elevated depressive symptoms, compared with those taking oral or no antidiabetes medication [8]. In contrast, we did not observe such a robust association between use of antidiabetes medication and depressive symptoms among people with diagnosed diabetes.…”
Section: Discussioncontrasting
confidence: 96%
“…In a large cross-sectional Chinese study, only people with previously known diabetes showed elevated depressive symptoms and more people treated with insulin showed elevated depressive symptoms, compared with those taking oral or no antidiabetes medication [8]. In contrast, we did not observe such a robust association between use of antidiabetes medication and depressive symptoms among people with diagnosed diabetes.…”
Section: Discussioncontrasting
confidence: 96%
“…The highest prevalence was based on the BDI, cut-off ≥ 10 (n = 17 participants) [29]. The lowest prevalence was based on the PHQ-9, cut-off ≥ 10 (n = 229 047) [30] and in a separate study by the BDI-II, cut-off ≥ 20 (n = 5145) [31].…”
Section: Resultsmentioning
confidence: 99%
“…The paper also reported that the odds of depression were not higher in individuals with screening diagnosed type 2 diabetes or impaired glucose metabolism (pre-diabetes) compared with those with normal glucose metabolism [13]. A Chinese study also concluded that, compared with people with normal glucose regulation (n = 120 458), people with diabetes (n = 24 251) had higher odds of probable diagnosis of depression (1.61, 95% CI 1.39-1.87) and sub-threshold depression [odds ratio (OR) = 1.14, 95% CI 1.06-1.24], whereas newly diagnosed diabetes (n = 24 826) or impaired glucose regulation (n = 59 512) were not associated with depression [16].…”
Section: The Prevalence Of Depression In Diabetesmentioning
confidence: 99%